Civilization within the heart: the image and meaning of 'civilization' and 'culture' in Chinese characters. Issue 1 (13th April 2022) - Shen, Heyong
Abstract: 'Civilization in Transition' was the theme of the JAP conference in 2021, and also the reality we are facing today, especially amidst the pandemic of COVID‐19. From an oriental perspective, within the context of Psychology of the Heart, the author presents his thoughts in this paper, 'Civilization within the heart: the image and meaning of "civilization" and "culture" in Chinese characters'. The meaning of the heart is at the core of Chinese culture, as well as Chinese philosophy and psychology. Most of the basic psychological terms in Chinese characters are formed originally with the images of the heart; even the Chinese character for 'culture' and 'civilization'. C.G. Jung learned Chinese characters, and named them with I Ching symbols as readable archetypes. Today in world affairs we are confronted with highly turbulent and uncertain conditions that threaten any sense of coherent meaning, both personally and collectively. Jung's insights gained from the I Ching and his reflections on analytical psychology are still inspiring us. The images and meaning of the hexagrams which C.G. Jung used: 'Ting' (The Cauldron), 'Bi' (Grace), and 'Chin' (Progress), are the main threads of this paper and presentation, 'Civilization within the Heart', responding to the theme 'Civilization in Transition'. Abstract : « La civilisation en transition » est le thème de la conférence du JAP en 2021, et également la réalité à laquelle nous faisons face aujourd'hui, particulièrement avec la pandémie de COVID‐19. A partir d'une perspective orientale, dans le contexte de la Psychologie du Cœur, l'auteur présente ses pensées dans cet article « La civilisation à l'intérieur du cœur: l'image et le sens de 'civilisation' et de 'culture' dans les caractères chinois ». La signification du cœur est centrale à la culture chinoise, et à la philosophie et la psychologie chinoises. La plupart des termes psychologiques fondamentaux en caractères chinois sont à l'origine formés avec les images du cœur; même ceux pour «culture» et pour «civilisation». C.G. Jung a appris les caractères chinois, et les a nommés avec les symboles du Yi Jing en tant qu'archétypes lisibles. Aujourd'hui dans les affaires du monde nous sommes confrontés à des conditions hautement turbulentes et incertaines qui menacent toute cohérence de sens, aussi bien au niveau personnel que collectif. Les éclairages de Jung provenant du Yi Jing et ses réflexions sur la psychologie analytique nous inspirent encore. Les images et la signification des hexagrammes que Jung a utilisés: 'Ting' (Le Chaudron), 'Pi' (La grâce), et 'Tsien' (Le Progrès), sont les fils conducteurs principaux de cet article et présentation: « La civilisation à l'intérieur du cœur », pour répondre au thème de « Civilisation en Transition ». Abstract : 'Zivilisation im Übergang' bezeichnet das Thema der JAP‐Konferenz im Jahr 2021 und auch die Realität, mit der wir heute konfrontiert sind, insbesondere inmitten der COVID‐19‐Pandemie. Aus fernöstlicher Perspektive im Kontext der Psychologie des Herzens betrachtet, präsentiert der Autor seine Gedanken in diesem Artikel 'Zivilisation im Herzen: das Bild und die Bedeutung von 'Zivilisation' und 'Kultur' in chinesischen Schriftzeichen'. Die Bedeutung des Herzens bildet den Kern der chinesischen Kultur sowie der chinesischen Philosophie und Psychologie. Die meisten grundlegenden psychologischen Begriffe in chinesischen Schriftzeichen werden ursprünglich mit den Bildern des Herzens gebildet; sogar das chinesische Schriftzeichen für 'Kultur' und 'Zivilisation'. C.G. Jung lernte chinesische Schriftzeichen und benannte sie mit I Ging ‐Symbolen als lesbare Archetypen. Heute sind wir im Weltgeschehen mit höchst turbulenten und unsicheren Bedingungen konfrontiert, die jeden Sinn für kohärente Bedeutung, sowohl persönlich als auch kollektiv, bedrohen. Jungs aus dem I Ging gewonnenen Erkenntnisse und seine Überlegungen zur Analytischen Psychologie inspirieren uns noch immer. Die Bilder und die Bedeutung der Hexagramme, die C.G. Jung verwendete: 'Ting' (der Kessel), 'Bi' (Gnade) und 'Chin' (Fortschritt), sind die Hauptthemen dieses Artikels und der Präsentation, 'Zivilisation im Herzen', womit auf das Thema 'Zivilisation im Übergang' reagiert werden soll. Abstract : 'Civiltà in Transizione' è il tema della conferenza JAP 2021, così come la realtà che stiamo affrontando oggi, specialmente durante la pandemia da COVID‐19. Da una prospettiva orientale, nel contesto della Psicologia del Cuore, l'Autore presenta i suoi pensieri in questo articolo, 'Civiltà nel cuore: l'immagine e il significato di "civiltà" e "cultura" nei caratteri cinesi'. Il significato del cuore è alla base della cultura cinese, così come della filosofia e psicologia cinesi. La maggior parte dei termini psicologici di base nei caratteri cinesi sono formati originariamente con le immagini del cuore; perfino il carattere cinese per 'cultura' e 'civiltà'. Jung imparò i caratteri cinesi e li definì archetipi leggibili, insieme ai simboli dell' I Ching . Oggi sulla scena internazionale ci troviamo di fronte a condizioni altamente turbolente ed incerte che mettono a repentaglio qualsiasi senso di significato coerente, sia a livello personale che collettivo. Le intuizioni di Jung tratte dall' I Ching e le sue riflessioni sulla psicologia analitica ci stanno ancora ispirando. Le immagini ed i significati degli esagrammi usati da Jung: 'Ting' (Il Calderone), 'Bi', (Grazia), e 'Chin' (Progresso), sono i fili principali di questo articolo 'Civiltà nel Cuore', per rispondere al tema 'Civiltà in Transizione'. Abstract : «Цивилизация в переходный период» ‐ это тема конференции JAP в 2021 году, а также реальность, с которой мы сталкиваемся сегодня, особенно в условиях пандемии COVID‐19. С восточной точки зрения, в контексте «Психологии сердца» автор излагает свои мысли в этой статье. Значение сердца лежит в основе китайской культуры, а также китайской философии и психологии. Большинство психологических терминов китайских иероглифов изначально образованы образами сердца; даже китайский иероглиф «культура» и «цивилизация». К.Г. Юнг выучил китайские иероглифы и назвал их символами И Цзин как читаемые архетипы. Сегодня в мировых делах мы сталкиваемся с крайне неспокойными и неопределенными условиями, которые угрожают любому чувству связного смысла как лично, так и коллективно. Понимание Юнга, полученное из И‐Цзин, и его размышления об аналитической психологии до сих пор вдохновляют нас. Образы и значение гексаграмм, которые К. Юнг использовал: «Тинг» (Котел), «Би» (Грейс) и «Чин» (Прогресс) ‐ основные темы этой статьи и презентации «Цивилизация в сердце» как ответ на тему «Цивилизация в переходный период». Abstract : 'Civilización en Transición' es el tema de la Conferencia del JAP en 2021, y también la realidad que estamos enfrentando hoy, especialmente en medio de la pandemia de COVID‐19. Desde una perspectiva oriental, en el contexto de la Psicología del Corazón, el autor ofrece su reflexión en el presente trabajo, 'Civilización en el corazón: la imagen y el sentido de la 'civilización' y la 'cultura' en los caracteres chinos'. El sentido del corazón está al centro de la cultura China, así como también de la psicología y filosofía China. La mayoría de los términos psicológicos básicos en los caracteres chinos están formados originalmente con las imágenes del corazón; aún el signo chino para 'cultura' y 'civilización'. C. G. Jung aprendió los caracteres chinos, y los denominó junto a los símbolos del I Ching como arquetipos legibles. Actualmente, estamos siendo confrontados a nivel mundial con condiciones excesivamente turbulentas e inciertas que amenazan cualquier sentido de coherencia, tanto personal como colectivamente. Las comprensiones que Jung tomó del I Ching y sus reflexiones en la psicología analítica aún hoy nos inspiran. Las imágenes y el sentido de los hexagramas que Jung usó: 'Ting' (El Caldero), 'Bi' (Gracia), y 'Chin' (El Progreso), son las hebras principales de este trabajo y presentación, 'Civilización en el Corazón', respondiendo al tema 'Civilización en Transición'. Abstract : 寓心之文:文明的意象与意义及汉字中的"文化" "转变中的文明"是 2021年 JAP 会议的主题, 也是我们今天面临的现实, 尤其是在新冠疫情的大流行中。从东方的角度, 在核心心理学的语境下, 作者在《文明的意象与意义及汉字中的"文化" 》一文中提出了自己的想法。心的意义是中国文化的核心, 也是中国哲学和心理学的核心。汉字中有一大部分字形, 最初都是由心的意象构成的；甚至"文化"和"文明"的汉字亦如此。荣格学习了汉字, 并用易经象征来命名它们, 把它们当作可读的原型。今天, 我们在世界各地都面临着高度动荡和不确定, 威胁着个人和集体的所有凝聚的意义感。荣格从《易经》中获得的见解和他对分析心理学的思考仍然激励着我们。 荣格所用的《易经》卦象及其意义:鼎卦、贲卦、晋卦, 将是这篇论文的主要线索, "寓心之文", 以回应此届大会的主题:"转变中的文明"。 Abstract : 'Civilização em Transição' é o tema da conferência do JAP em 2021, e também a realidade que enfrentamos hoje, especialmente em meio à pandemia de COVID‐19. De uma perspectiva oriental, dentro do contexto da Psicologia do Coração, o autor apresenta seus pensamentos neste artigo, 'Civilização dentro do coração: a imagem e o significado de "civilização" e "cultura" em caracteres chineses'. O significado do coração está no centro da cultura chinesa, assim como da filosofia e psicologia chinesas. A maioria dos termos psicológicos básicos em caracteres chineses é formado originalmente com as imagens do coração; até mesmo o caractere chinês para "cultura" e "civilização". C.G. Jung aprendeu caracteres chineses e os nomeou com símbolos I Ching como arquétipos legíveis. Hoje, nos assuntos mundiais, somos confrontados com condições altamente turbulentas e incertas que ameaçam qualquer senso de significado coerente, tanto pessoal quanto coletivamente. Os insights de Jung obtidos com o I Ching e suas reflexões sobre psicologia analítica ainda estão nos inspirando. As imagens e o significado dos hexagramas que C.G. Jung usou: 'Ting' (O Caldeirão), 'Bi' (Graça) e 'Chin' (Progresso), são os principais tópicos deste artigo e apresentação, 'Civilização dentro do Coração', para responder ao tema 'Civilização em Transição'.